2017
DOI: 10.4269/ajtmh.16-0227
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical and Laboratory Alterations Related to Dengue Case Severity: Comparison between Serotypes 2 and 4 in Brazil

Abstract: The increase in severe dengue (SD) cases has caused great impact on public health and has concerned authorities of countries where the disease is endemic and epidemics reach high proportions. The recognition of progression signs of this severe disease during the initial febrile phase can be difficult, since the symptoms are often indistinguishable from other febrile diseases. The aim of this study was to evaluate the clinical manifestations and laboratory findings in patients from two dengue outbreaks and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“… 34 Similarly, a prospective study in central Brazil showed that among 253 cases of laboratory-confirmed dengue that occurred between January 2012 and July 2013, DENV-4 was detected in the 55.6% of cases, DENV-1 in 37.4%, DENV-3 in 5.3%, and DENV-2 in 1.6% of cases. 35 Most children were naive to DENV-4 at the beginning of the study, although there is evidence that some children already had detectable neutralizing antibodies against this serotype at the end of 2011.…”
Section: Discussionmentioning
confidence: 98%
“… 34 Similarly, a prospective study in central Brazil showed that among 253 cases of laboratory-confirmed dengue that occurred between January 2012 and July 2013, DENV-4 was detected in the 55.6% of cases, DENV-1 in 37.4%, DENV-3 in 5.3%, and DENV-2 in 1.6% of cases. 35 Most children were naive to DENV-4 at the beginning of the study, although there is evidence that some children already had detectable neutralizing antibodies against this serotype at the end of 2011.…”
Section: Discussionmentioning
confidence: 98%
“…In 2012, DENV-4 was prevalent and detected in 63% of the cases reported in Brazil [7]. Despite the highest notification in 2013 (1,452,289 cases), DENV-4 circulation was associated with mild cases [8,9], but severe and fatal cases due to DENV-4 were also reported [10]. Although there has been no definitive association of the different DENV serotypes within the clinical course of the disease, it has been suggested that DENV-2 and DENV-3 are more frequently associated with severe disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, the DENV-4 genotype II was the most prevalent serotype [ 10 , 11 ] in an explosive epidemic that caused a high number of cases and deaths, mainly in the states of the southeastern and central-western regions [ 12 , 13 ]. Although the majority of DENV-4 infections were generally characterized by mild clinical pictures compared to other serotypes [ 14 ], severe cases and deaths due to DENV-4 were reported [ 15 ]. Thus, the impact that the re-emergence of DENV-4 had in this endemic country is still not well understood, and studies that include the evaluation of the inflammatory response are necessary.…”
Section: Introductionmentioning
confidence: 99%